2006
DOI: 10.1111/j.1475-6773.2006.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Take‐up by the Near‐Elderly

Abstract: The implied elasticities are comparable with results found in previous studies using very different data. Our estimates indicate that policy proposals for a Medicare buy-in or a nongroup tax credit will have a modest impact on take-up rates of near-elderly retirees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Yearly renewable term life insurance, USA −0.4 to −0.5 Pauly et al (2003) Term life insurance { XE "term life insurance" }, USA −0.66 Viswanathan et al (2007) Whole life insurance, USA −0.71 to −0.92 Babbel (1985) Health insurance { XE "health insurance" }, USA 0 to −0.2 Chernew et al (1997); Blumberg et al (2001); Buchmueller and Ohri (2006) Health insurance, Australia −0.35 to −0.50 Howeverler (1999) Farm { XE "crop insurance" } crop insurance, USA −0.32 to −0.73 Goodwin (1993) Note: Demand elasticities are all given with a minus sign because a rise in price implies a fall in demand.…”
Section: Market and Country Estimated Demand Elasticities Authorsmentioning
confidence: 99%
“…Yearly renewable term life insurance, USA −0.4 to −0.5 Pauly et al (2003) Term life insurance { XE "term life insurance" }, USA −0.66 Viswanathan et al (2007) Whole life insurance, USA −0.71 to −0.92 Babbel (1985) Health insurance { XE "health insurance" }, USA 0 to −0.2 Chernew et al (1997); Blumberg et al (2001); Buchmueller and Ohri (2006) Health insurance, Australia −0.35 to −0.50 Howeverler (1999) Farm { XE "crop insurance" } crop insurance, USA −0.32 to −0.73 Goodwin (1993) Note: Demand elasticities are all given with a minus sign because a rise in price implies a fall in demand.…”
Section: Market and Country Estimated Demand Elasticities Authorsmentioning
confidence: 99%
“…A questionnaire survey about life insurance purchasing decisions produced an estimate of -0.66 (Viswanathan et al, 2007). For private health insurance in the US, several studies estimate demand elasticities in the range of 0 to -0.2 (Chernew et al, 1997;Blumberg et al, 2001;Buchmueller and Ohri, 2006). For private health insurance in Australia, Butler (1999) estimates demand elasticities in the range -0.36 to -0.50 (higher than in the US, perhaps because Australia's universal Medicare is a better substitute for private insurance than is available to most people in the US).…”
Section: Comparison With Empirical Demand Elasticitiesmentioning
confidence: 99%
“…Three other assessments showed that many children leaving state CHIP coverage lost any form of insurance [ 3 - 5 ]. Other studies documented a drop in health insurance coverage in response to rising premiums using different data sets [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%